Factors Influencing Impulsive Purchase Behavior in Livestreaming E-Commerce - Mokodaser, Livia Prisillia; Elistia, Elistia (Journal of Business and Economics Research (JBE), 2024)
The continued growth of e-commerce live streaming is essential for e-commerce marketers in understanding the factors that influence the impulse buying behavior of live streaming shopping. This study analyzes the effect of perceived e-commerce anchor attributes, perceived scarcity, and immersion on consumer trust and impulsive purchase behavior in e-commerce live streaming. This research was conducted in Jakarta using a descriptive causality research design with a quantitative method approach and a purposive sampling technique. Data was collected from 352 respondents who had used the e-commerce live-streaming application in Jakarta. The conceptual model was analyzed using Structural Equation Modeling. The results of this study indicate that perceived e-commerce anchor attributes, perceived scarcity, and immersion can increase consumer trust and impulsive purchase behavior, consumer trust can increase impulsive purchase behavior. Furthermore, a personal sense of power has moderation which can improve the relationship between consumer trust and impulsive purchase behavior. The contribution of this research can provide insights to businesses in the e-commerce live-streaming industry to direct consumer buying behavior more effectively, increase impulse buying participation, and achieve sustainable success.